How to do an open midline extraperitoneal bilateral retroperitoneal lymph node dissection for non‐seminomatous germ cell tumour. Issue 1 (30th November 2022) - Parkin, Cameron James; Sharma, Aditya; Winter, Matthew
Abstract : Retroperitoneal lymph node dissection, remains a crucial step in the management of patients with non‐seminomatous germ cell tumours who have undergone chemotherapy. It is a technically challenging operation with a number of techniques that have been advocated. We outline the midline, extraperitoneal approach to perform a bilateral template lymph node dissection.